Impact of smoking cessation, coffee and bread consumption on the intestinal microbial composition among Saudis: A cross-sectional study. - Steve Harakeh; Emmanouil Angelakis; Timokratis Karamitros; Dipankar Bachar; Suhad Bahijri; Ghada Ajabnoor; Sulaiman M Alfadul; Suha A Farraj; Turki Al Amri; Ahmed Al-Hejin; Abdalla Ahmed; Ahmed A Mirza; et al. (PLoS ONE)
The gut microbiota is often affected by the dietary and lifestyle habits of the host, resulting in a better efficacy that favors energy harvesting from the consumed food. Our objective was to characterize the composition of gut microbiota in adult Saudis and investigate possible association with lifestyle and dietary practices. Feces from 104 Saudi volunteers (48% males) were tested for microbiota by sequencing the V3-V4 region of bacterial 16S ribosomal RNA (rRNA). For all participants, data were collected related to their lifestyle habits and dietary practices. The relative abundance (RA) of Fusobacteria was significantly higher in normal weight Saudis (P = 0.005, false discovery rate-FDR = 0.014). Individuals who consumed more coffee presented marginally significant more RA of Fusobacteria (P = 0.02, FDR = 0.20) in their gut microbiota compared to those reporting low or no coffee intake, but the RA of Fusobacteria was significantly higher in smokers compared to non-smokers (P = 0.009, FDR = 0.027). The RA of Fusobacteria was also significantly higher in those reporting daily consumption of bread (P = 0.005, FDR = 0.015). At the species level, the gut microbiota of people who consumed coffee was dominated by Bacteroides thetaiotaomicron followed by Phascolarctobacterium faecium and Eubacterium rectale. Similarly, the gut microbiota of smokers was also enriched by B. thetaiotaomicron and Lactobacillus amylovorus. Smoking cessation, bread and coffee consumption induce changes in the intestinal microbial composition of Saudis. This indicates the significance of diet and lifestyle practices in the determination of the composition of the gut microbiota, which could possibly lead later to changes in metabolic profile and weight.